2013
DOI: 10.1111/1471-3802.12002
|View full text |Cite
|
Sign up to set email alerts
|

Professional development for specialist teachers and assessors of students with literacy difficulties/dyslexia: ‘to learn how to assess and support children with dyslexia’

Abstract: In this paper, the results of an investigation into the training needs and expectations of participants of professional development training1 for specialist teachers and assessors of learners with literacy difficulties and dyslexia are discussed and analysed. The methodology includes both qualitative and quantitative data which were collected over a period of 2 years from participants (N = 75) at the beginning of their courses of study. Current literature is reviewed, and an in‐depth analysis of the findings i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 24 publications
1
10
0
3
Order By: Relevance
“…Unfortunately, as many as 92% of teachers indicated that they lack the specific knowledge necessary to implement this type of instruction with students with dyslexia (Bell, 2013; Fielding‐Barnsley & Purdie, 2005; Moats & Foorman, 2003; Moreau, 2014; Shetty & Rai, 2014). They also report frustration when teaching students with dyslexia in the general education classroom (Wadlington & Wadlington, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, as many as 92% of teachers indicated that they lack the specific knowledge necessary to implement this type of instruction with students with dyslexia (Bell, 2013; Fielding‐Barnsley & Purdie, 2005; Moats & Foorman, 2003; Moreau, 2014; Shetty & Rai, 2014). They also report frustration when teaching students with dyslexia in the general education classroom (Wadlington & Wadlington, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Teachers also report that the professional development they receive once they enter the classroom is not adequate, with these professional development opportunities being one‐time events rather than being sustained throughout the school year (Chambers & Hausman, 2014). Additionally, these opportunities lack instruction in strategies that would be effective for students with dyslexia, indicating the need for more applicable professional development (Bell, 2013; Chambers & Hausman, 2014; Moats & Foorman, 2003). Providing this appropriate professional development, ultimately, is the responsibility of the school administrators (Lunenburg & Ornstein, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…This important issue of facilitative or hindering factors in a school's climate was noted in Symes and Humphrey's (2011) study of how TAs support for autistic students, though this was not linked to any measure of the impact of any specialist training. Bell (2013) interviewed teachers and TAs embarking on specialist training to support dyslexic pupils and noted their desires to develop knowledge of dyslexia and its assessment. However, these data were drawn from respondents just beginning training and there is currently a lack of knowledge about not only the impact the completion of specialist dyslexia training upon TAs' professional expertise and practice and whether they are actually being deployed in the specialist role, but also the wider impact of having such a trained specialist on the staff upon the development of dyslexia-friendly practice at whole-school level.…”
Section: The Development Of the Ta Rolementioning
confidence: 99%
“…The head of the centre commented that this was a challenge within the region: ‘ trying to keep up with current thinking and developments, being out in Asia, it's hard ’. Research has shown that training and professional development for teachers is important to provide skilled dyslexia support (Bell, ). One main obstacle that the centre tries to overcome is that of ensuring the professionals at the centre maintain up‐to‐date knowledge and skills.…”
Section: Collaboration Competencies and Skills Of Professionalsmentioning
confidence: 99%